STUDY OF BAROMBONG RAW WATER NEEDS, GOWA REGENCY - Ratna Musa; Abd Karim Hadi Hadi; Andi R Tenri Pakkua Tenri Pakkua (Moeslim Indonesian University (UMI), 2020)
Clean water is a primary human need where there are many uses such as drinking, cooking, bathing and others. Population growth in an area that is increasing year by year has resulted in a large number of public demands related to the need for clean water. The purpose of writing is to find out the availability of raw water and the need for clean water in the Barombong sub-district in the next 5 (five) years. In analyzing the data, there are several stages that are passed, namely analyzing the population for the next five years using arithmetic, geometric and linear regression methods, and analyzing raw water sources using the Fj method. Mock and raw water needs. After analyzing the data, it can be described that the potential need for raw water in the Barombong sub-district for the next 5 (five) years is very sufficient where the availability of raw water is 176.01 Ltr/s while the need is 118.24 Ltr/s.